Análisis comparativo de los activos intangibles según la NIC38 y los artículos 66 y 67 del Decreto 2649 de 19931 (2014)
From a theoretical point of view, the aim of this article is to show the main similarities and differences between the International Accounting Standard (IAS) 38: Intangible Assets and the Decree 2649 of 1993, considering the huge amount of guidelines that it can cover. In order to explain the similarities and differences, a reading of each standard to be applied was made and a set of benchmarks related to the inspection, measurement and presentation of the intangible assets in the basic financial statements of a company was established. Keep in mind that the IAS 38 is not a starting point for the financial information because, as I will explain later, Colombian standards aren’t as explicit as the AIS ones.